THE EMERGENCE OF A MEDICAL SPECIALTY (WITH PARTICULAR REFERENCE TO NEUROSURGERY). PART I. SOCIAL-HISTORICAL FACTOR - B. L. Liсhterman (Сеченовский вестник, 2022)
This is a first part of an article which treats specialization in medicine using a system approach. Three main systemic factors (we called them discipline-making factors) are crucial for the emergence of a clinical specialty (in our case this specialty is neurosurgery): social-historical, scientific and institutional. This paper is dedicated to social-historical factor which includes level of society development (industrialization, urbanization and level of university education) and wars. The impact of World War I on subsequent birth of neurosurgery as a separate specialty in Europe and USA is demonstrated.